2017
DOI: 10.2741/4557
|View full text |Cite
|
Sign up to set email alerts
|

Substance use disorder a bio-directional subset of reward deficiency syndrome

Abstract: This commentary is to inform clinicians challenged with an increase in people seeking treatment for Substance Use Disorder (SUD), that the ninety percent revolving door, is, in part, due to post-withdrawal, untreated neurotoxicity. This impairment attenuates neurotransmitter signaling and compromises resting state functional connectivity, leading to unwanted sequelae including depression, sleep disturbances, sensation seeking, lack of satisfaction and impulsivity. Neuroimaging studies indicate that neurobiolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 65 publications
0
16
0
Order By: Relevance
“…The eCB system is clearly tied in the regulation of reward- related behavior, ethanol consumption and potentially in reward deficiency syndrome [ 42 ]; however, relatively little is known about these interactions (for a review, see [ 5 , 43 ]. The current study has demonstrated that the administration of FABP5/7 inhibitor, SBFI26, decreased consumption in both males and females by 24% ( p < 0.05) and 42% ( p < 0.001) less when compared to the group receiving no injections.…”
Section: Discussionmentioning
confidence: 99%
“…The eCB system is clearly tied in the regulation of reward- related behavior, ethanol consumption and potentially in reward deficiency syndrome [ 42 ]; however, relatively little is known about these interactions (for a review, see [ 5 , 43 ]. The current study has demonstrated that the administration of FABP5/7 inhibitor, SBFI26, decreased consumption in both males and females by 24% ( p < 0.05) and 42% ( p < 0.001) less when compared to the group receiving no injections.…”
Section: Discussionmentioning
confidence: 99%
“…Despite attempts to remain abstinent, one- to two- thirds of individuals who complete treatment programs report relapsing even within just a few months after completion [2, 4]. Stress and negative affect, including that which is associated with withdrawal, are major factors leading to relapse [58] and are linked in general to reward deficiency syndrome [9, 10]. It has been shown that cocaine-dependent individuals exhibit altered neural, behavioral, and physiological responses to stressful stimuli [1114], and that the magnitude of neural, physiological, and behavioral reactivity to stressors are correlated with rehabilitation program dropout rates, stress-induced drug cravings, and relapse behaviors [3, 4, 13, 1518].…”
Section: Introductionmentioning
confidence: 99%
“…To understand the COMT-cannabis-psychosis/AoP relationship, it is important to consider the following. Dopamine plays a role in psychosis (Howes, McCutcheon, Owen, & Murray, 2017) and in cannabis use (Blum et al, 2017). A genome-wide association study reported the D 2 receptor gene (DRD2) as one of the 108 loci associated with schizophrenia (Schizophrenia Working Group of the Psychiatric Genomics C, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Dopaminergic agonists and stimulants worsen psychosis (Angrist & Gershon, 1970), while dopamine receptor (D 2 /D 3 ) antagonism is key to reducing symptoms of psychosis (Howes et al, 2009;Seeman, Lee, Chau-Wong, & Wong, 1976). Substance misuse, including cannabis, is linked to reward mechanisms, in which dopamine plays a central role (Blum et al, 2015(Blum et al, , 2017. There is significant interaction between dopamine and the endogenous cannabinoid system (ECS) in substance misuse.…”
Section: Introductionmentioning
confidence: 99%